Emerging frontiers in drug release control by core–shell nanofibers: a review. (2nd October 2019) - Monfared, Mohammad; Taghizadeh, Saeed; Zare-Hoseinabadi, Alireza; Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza; Ranjbar, Saba; Amani, Ali Mohammad
Abstract: In recent years, core–shell (CS) nanofiber has widely been used as a carrier for controlled drug release. This outstanding attention toward CS nanofiber is mainly due to its tremendous significance in controllable drug release in specific locations. The major advantage of CS nanofibers is forming a highly porous mesh, boosting its performance for many applications, due to its large surface-to-volume ratio. This inherently high ratio has prompted electrospun fibers to be considered one of the best drug-delivery-systems available, with the capacity to enhance properties such as cell attachment, drug loading, and mass transfer. Using electrospun fibers as CS nanofibers to incorporate different cargos such as antibiotics, anticancer agents, proteins, DNA, RNA, living cells, and diverse growth factors would considerably satisfy the need for a universal carrier in the field of nanotechnology. In addition to their high surface area, other benefit included in these nanofibers is the ability to trap drugs, easily controlled morphology, and their biomimetic characteristics. In this review, by taking the best advantages of the preparation and uses of CS nanofibers, a novel work in the domain of the controlled drug delivery by nanofiber-based scaffolds is presented.